Study the Implementation of Education Quality Assurance in Pasatipaatai Secondary School in Luang Prabang District - vongphachanh, vongphiboun; KOUNLASAY, Kalaphath; THIPPHAPHONE, Kinnaly; KONEPHACHITH, Domone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research aims to 1) study the implementation of quality assurance in Pasathipatai secondary schools in Luang Prabang and 2) determine the guidelines for quality assurance in Pasathipatai secondary schools in Luang Prabang. The sample group of 46 people consisted of 3 administrators and 43 teachers by finding the mean and standard deviation. The results of the research found that overall, it was at a high level with a mean value of (= 4.07; S.D= 0.41). The guidelines for implementing education quality assurance at the Pasathipatai School in Luang Prabang can be seen in six aspects: students, teaching and learning, environment, teaching and learning equipment, management and administration and community participation. It was found that there should be promotion and motivation for students to be interested in coming to school regularly, compete with each other, and strictly follow school rules. Teachers should have a variety of teaching techniques to convey knowledge to students, select teachers who are qualified and equipped in all aspects, praise teachers who teach well and are good at creating achievements for the school and send them to upgrade to develop higher academic and technological skills. Encourage students to know how to care for the environment and arrange the school yard to be clean and attractive. School administrators should inspect the condition of classroom equipment and provide sufficient necessary equipment, use libraries, real-time experimental tools and computers in conjunction with teaching and learning, encourage teachers to produce more teaching and learning media and have a focused school development plan with a short-term and long-term perspective, providing opportunities for teachers to participate in planning discussions to properly. administrators should work closely with associations, parents, and village-level education development committees to help mobilize the community to participate, contribute to school support and see the importance of education.